EVALUATING THE TIMING OF OIL EXPULSION: ABOUT THE INVERSE BEHAVIOUR OF LIGHT HYDROCARBONS AND OIL ASPHALTENE KINETICS - Dieckmann V.; Caccialanza P.G.; Galimberti R. (My University, 2002)
This paper deals with natural temperature records in the heavy (asphaltenes) and the light fractions (C7-light hydrocarbons) of petroleum. Two sets of marine oils formed from different source rocks and petroleum systems were studied using asphaltene kinetics and light hydrocarbon analysis. Both fractions have been reported to contain information about the temperature the respective oils have been exposed to in the subsurface. These indicated temperatures generally correspond to the conditions in the source rock when expulsion occurred. Bulk kinetic analysis of reservoir oil asphaltenes as well as light hydrocarbon (LH) analysis (of dimethylpentanes) were used here in order to evaluate the expulsion temperatures. Surprisingly, when considering information coming from both fractions, an inverse trend between LHs expulsion temperatures (Ctemp) and asphaltenes (Tasph.) can be observed-high Tasph (asphaltene temperatures) occur with low LH Ctemp (light hydrocarbon expulsion temperatures) and low Tasph can be observed when Ctemp is high. These differences are of fundamental importance for the use of such geochemical data in calibrating numerical basin models. The reason for this inverse behaviour is possibly due to the different expulsion behaviour of light hydrocarbons and the heavy fraction of oils, especially when the source rocks contain only moderate amounts of organic matter. In addition it has to be considered that the temperature predictions obtained using asphaltene kinetic analysis are related to the onset temperature of petroleum expulsion, while light hydrocarbons provide, at best, average expulsion temperatures.